2020
DOI: 10.1037/sah0000207
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental illness stigma among Hispanics: A systematic review.

Abstract: Stigma toward mental illness is a complex construct that impacts people's desire to seek mental health care and engage in treatment. Certain groups, including ethnic minorities, are disproportionately impacted by the effects of stigma. Among Hispanics, stigma has been found to be negatively associated with the desire to engage in mental health care, management of depression symptoms, disclosure of mental illness to family and friends, and adherence to antidepressant medications. The purpose of this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
0
18
2
Order By: Relevance
“…Research on psychometric properties of mental illness stigma measures among Hispanics is scarce, with few measures undergoing systematic psychometric validation [26]. In 2010, Interian et al [8] found evidence for the use of three different stigma measures with a sample of predominantly Spanish-speaking, Hispanic primary care patients (N = 200) who screened positive for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Research on psychometric properties of mental illness stigma measures among Hispanics is scarce, with few measures undergoing systematic psychometric validation [26]. In 2010, Interian et al [8] found evidence for the use of three different stigma measures with a sample of predominantly Spanish-speaking, Hispanic primary care patients (N = 200) who screened positive for depression.…”
Section: Introductionmentioning
confidence: 99%
“…We focus here on the role of cultural values pertinent to these ethnic groups on students' mental health help-seeking behaviors, complementing the extensive work on external barriers to seeking treatment including language or financial resources [6][7][8][9]. Though existing work has drawn connections between cultural values and mental health attitudes among both Asian and Latinx groups, the present work furthers the literature by examining shared values across groups [10,11]. Specifically, this study examined whether family-and group-oriented dimensions of cultural values that are shared among Asian and Latinx college students are associated with perceived need for mental health treatment and mental health help-seeking, above demographic characteristics.…”
mentioning
confidence: 99%
“…Despite the negative health impacts, many Latinos who experience depression or depression and diabetes and are in need of treatment do not actively seek professional help. Stigma toward mental illness is one of the most well-documented barriers to depression treatment among Latinos [9][10][11][12][13][14]. For many, the intersection of multiple marginalized identities (for example, being Latino, immigration status, and experiencing depression) may exacerbate the impact of mental health-related stigma [9].…”
mentioning
confidence: 99%
“…For many, the intersection of multiple marginalized identities (for example, being Latino, immigration status, and experiencing depression) may exacerbate the impact of mental health-related stigma [9]. Moreover, gender-based differences in expectations related to help seeking rooted in cultural values such as machismo (men being able to handle their own problems without external help), marianismo (self-sacrifice for those one cares about even to the detriment of oneself), as well as familismo (successfully fulfilling family obligations before all else) and fatalismo (accepting God's will or fate) may further impact Latinos' perceptions of people with depression [10,11] and also their willingness to seek professional help [12][13][14].…”
mentioning
confidence: 99%